Social cognition and prefrontal cognitive function in patients with epilepsy treated with eslicarbazepine acetate - Laura Abraira; Sanabria A; Ortega G; Quintana M; Santamarina E; Salas-Puig J; Toledo M (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2017)
Purpose: The purpose of this study was to evaluate the impact of treatment with eslicarbazepine acetate (ESL) on social cognition and prefrontal cognitive function in adults with partial onset seizures. Methods: A prospective, single-center, interventional study was conducted in patients aged 18 to 65 years with focal seizures, who received ESL. All patients were assessed using Theory of Mind (ToM) tasks (Eyes test and Faux Pas Recognition test), and evaluation of attentional and executive functions (Wisconsin Card Sorting test [WCST], Symbol Digit, Forward and Backward Digit Span, and Stroop tests), auditory-verbal memory (recognition and total learning memory test), quality of life (QOLIE-31 questionnaire), and anxiety/depression (Hospital Anxiety and Depression Scale [HADS]). Patients were evaluated before and at 6 months after starting ESL. Results: In total, 41 patients with partial onset epilepsy were prescribed ESL, and 30 completed the follow-up assessment. Results of the Eyes test (p=0.017) and Faux Pas Recognition test (p=0.002) showed a significant improvement in ToM tasks. On stratified analysis by gender, males experienced a greater improvement than females on both tests (p<0.001 and p=0.003, respectively). Cognitive improvement was seen in the WCST results (number of errors p=0.007, and number of perseverations p=0.010), Symbol Digit (p=0.004), Backward Digit Span (p=0.002), and Stroop test (p=0.031). No differences were found in the QOLIE-31 (p=0.145) or HADS (anxiety p=0.516, depression p=0.305) results. Improvements were independent of reductions in the number of seizures and ESL dosing. Conclusion: ESL treatment may improve some aspects of ToM in patients with epilepsy, specifically in males and regardless of seizure control, with no changes in quality of life, anxiety, or depression status